Power Shift in Taiwan and Its Implications on Cross-Strait Relations - Kasim, Kamer (Power Shifts in East Asia and Their Implications for Asia–Europe Relations, 2019)
Tsai Ing-wen of the DPP won the presidential elections on 16th January 2016 and was sworn in as Taiwan’s President on 20 May 2016. The discussions about the future of cross-strait relations started with reference to the previous DPP administration’s policy of 2000–2008. The tense cross-strait relations of the DPP era were replaced with more harmonious ones with Ma Ying-jeou of KMT from 2008 to 2016. KMT acted on the basis of the 1992 consensus. The change of power with the election of Tsai Ing-wen raised questions about the basis and continuation of the cross-strait dialogue. Tsai-Ing-wen in her inauguration speech pledged to maintain the existing mechanisms for dialogue and communication across the Taiwan Strait. She also emphasized that Taiwan would conduct cross-strait affairs in accordance with the Republic of China Constitution, the Act Governing Relations between the People of Taiwan Area and the Mainland Area, and other relevant legislation. The important question with regards to cross-strait relations is: how does China evaluate Tsai Ing-wen’s intentions about cross-strait relations and conduct its policies? In this paper the cross-strait policy of the new administration in Taiwan will be analyzed through DPP’s foreign policy. Since cross-strait relations cannot be analyzed just as a relation between Taiwan and China due to Taiwan’s ties with the US, the paper will also evaluate the new US administrations’ Taiwan policy. The cross-strait relations and the US regional role also have international implications due to the South and East China Sea dispute, which creates major security concerns.